Peripheral Blood RNA Expression Profiling in Illicit Methcathinone Users Reveals Effect on Immune System - Sikk, Katrin (Frontiers in Genetics, 2011)
Methcathinone (ephedrone) is relatively easily accessible for abuse. Its users develop an extrapyramidal syndrome and it is not known if this is caused by methcathinone itself, by side-ingredients (manganese), or both. In the present study we aimed to clarify molecular mechanisms underlying this condition. We analyzed whole genome gene expression patterns of peripheral blood from 20 methcathinone users and 20 matched controls. Gene expression profile data was analyzed by Bayesian modelling and functional annotation. In order to verify the genechip results we performed quantitative real-time (RT) PCR in selected genes. 326 out of analyzed 28,869 genes showed statistically significant differential expression with FDR adjusted p-values below 0.05. Quantitative RT-PCR confirmed differential expression for the most of selected genes. Functional annotation and network analysis indicated that most of the genes were related to activation “immunological disease, cellular movement and cardiovascular disease” gene network (enrichment score 42). As HIV and HCV infections were confounding factors, we performed additional stratification of patients. A similar functional activation of the “immunological disease” pathway was evident when we compared patients according to the injection status (past versus current users, balanced for HIV and HCV infection). However, this difference was not large therefore the major effect was related to the HIV status of the patients. Mn-methcathinone abusers have blood transcriptional patterns mostly caused by their HIV and HCV infections.